An essay on the appreciation of physical education as an applied science (Fiep Bulletin - online, 2015)
It is unquestionable that, since the second world war, physical education and sports have known a new soaring flight as much on the practical plan as on the theoretical plan. We shall deal here above all with the last aspect, i. e. the theory of physical education.